2014
DOI: 10.1093/fampra/cmu080
|View full text |Cite
|
Sign up to set email alerts
|

Empathy: what does it mean for GPs? A qualitative study

Abstract: The opinions of GPs in this research can be considered as supplementing and strengthening the findings of previous researches. The GPs in this study discussed, in particular, ideas important to the facilitation of empathy. These included: longer consultations, smaller practices, efficient telephonic triage by practice assistants, using intervision to help reflect on their work and drawing financiers' attention to the effectiveness of empathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 32 publications
1
40
0
Order By: Relevance
“…Extensive research has shown that physicians' affective communication (ie, being emotionally supportive and adopting a warm, empathic, and reassuring manner) may improve patients' outcomes, including decreased levels of anxiety and distress. 87,88 Physicians' affective communication not only tempers emotional arousal, but also enhances recall of medical information. 88 Research in various disorders has shown that such affective statements improved recall, especially with regard prognostic information and, to some extent, treatment information.…”
Section: Communication and Patient Participationmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive research has shown that physicians' affective communication (ie, being emotionally supportive and adopting a warm, empathic, and reassuring manner) may improve patients' outcomes, including decreased levels of anxiety and distress. 87,88 Physicians' affective communication not only tempers emotional arousal, but also enhances recall of medical information. 88 Research in various disorders has shown that such affective statements improved recall, especially with regard prognostic information and, to some extent, treatment information.…”
Section: Communication and Patient Participationmentioning
confidence: 99%
“…87,88 Physicians' affective communication not only tempers emotional arousal, but also enhances recall of medical information. 88 Research in various disorders has shown that such affective statements improved recall, especially with regard prognostic information and, to some extent, treatment information. Obviously, because sarcoidosis requires a multidisciplinary approach in view of its wide range of symptoms, communication among the various health care workers involved and between them and the patients is of great importance.…”
Section: Communication and Patient Participationmentioning
confidence: 99%
“…Empathy has been shown to contribute substantially to building and maintaining a good patient-physician relationship [4]. Studies on empathy among general practitioners (physicians specialised in general practice) concluded that a general practitioner's display of empathy creates a relationship built on trust, openness, and safety and that a general practitioner's empathic attitude makes the patient feel supported and listened to [5,6]. Consequently, patients are more likely to disclose accurate and important information about themselves resulting in better diagnostics and clinical outcomes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond clinical outcomes, empathic communication has been shown to enhance patient satisfaction, compliance and patient empowerment [10][11][12]. Additionally, regarding physicianrelated benefits of empathy, physicians who perceive themselves as being empathic experience empathy as a source of professional satisfaction and meaningfulness protecting against burn-out [5,13,14]. As an offshoot of the large body of research documenting the beneficial effects of physician empathy, empathy development among medical students has become a comprehensive research topic.…”
Section: Introductionmentioning
confidence: 99%
“…Defined in the medical literature as the ability to understand a patient's suffering and concerns combined with an ability to communicate this understanding and an intention to help [5][6][7], clinical empathy has been associated with a number of beneficial patient and physician outcomes: more accurate diagnosis and treatment, increased patient satisfaction and compliance [6,[8][9][10][11], lower incidence of complaints and lawsuits, and lower levels of burnout and stress among physicians [5,12,13]. Moreover, high scores on empathy among medical students are associated with the following positive outcomes: increased satisfaction with their education, lower levels of stress and burn-out, higher ratings of overall clinical competences given by medical school faculty, better interpersonal skills assessed by patients and greater teamwork skills [5,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%